Analysis of Patents Issued in China for Antihyperglycemic Therapies for Type 2 Diabetes Mellitus - Zhu, Wei; Huang, Wen; Xu, Zhiqiang; Cao, Mengda; Hu, Qiaoli; Pan, Chen; Guo, Miao; Wei, Ji-Fu; Yuan, Hongyu (Frontiers in Pharmacology, 2019)
Type 2 diabetes mellitus (T2DM) is prevalent, with a dramatic increase in recent years. Moreover, its microvascular and macrovascular complications cause significant societal issues. The demand for new and effective antidiabetic therapies grows with each passing day and motivates organizations and individuals to pay more attention to such products. In this article, we focused on oral antihyperglycemic drugs patented in China and introduced them according to their antihyperglycemic mechanisms. By searching the website of State Intellectual Property Office of the People's Republic of China (http://www.sipo.gov.cn), 2500 antihyperglycemic patents for T2DM were identified and analyzed. These consisted of 4 patents for derivatives of herbal extracts (0.2%), 162 patents for herbal extracts (6.5%), 61 compositions for traditional Chinese medicine (TCM) (2.4%), 2263 patents for synthetic compounds (90.5%) and 10 (0.4%) patents of the combination of synthetic compounds and TCM. As the most common drugs for diabetes mellitus, synthetic compounds can also be classified into several categories according to their working mechanisms, such as insulin secretion promotor agents, insulin sensitizer agents, α-glucosidase inhibitors and so forth. This article discussed the chemical structure, potential antihyperglycemic mechanism of these antihyperglycemic drugs in patents in China.